Loss aversion and intertemporal choice: A laboratory investigation - Robert J. Oxoby; William G. Morrison (Institute for the Study of Labor (IZA), 2010)
We present results from a laboratory study of loss aversion in the context of intertemporal choice. We investigate whether the provision of (windfall) endowments results in different elicited discount rates relative to subjects who earn income or earn and retain the income for a period before making intertemporal decisions. We hypothesize that loss aversion in an intertemporal choice yields higher discount rates among subjects earning and retaining. Our results support this hypothesis: among subjects who earn and retain their income we elicit substantially higher discount rates relative to those experiencing a windfall gain.
Keywords: C91; D91; 330; Intertemporal choice; discount rates; experiments; Einkommen; Zeitpräferenz; Risikoaversion; Abzinsung; Test